Integrating Traditional Ecological Knowledge and Ecological Science: a Question of Scale - Catherine A. Gagnon; Dominique Berteaux (Ecology and Society, 2009)
The benefits and challenges of integrating traditional ecological knowledge and scientific knowledge have led to extensive discussions over the past decades, but much work is still needed to facilitate the articulation and co-application of these two types of knowledge. Through two case studies, we examined the integration of traditional ecological knowledge and scientific knowledge by emphasizing their complementarity across spatial and temporal scales. We expected that combining Inuit traditional ecological knowledge and scientific knowledge would expand the spatial and temporal scales of currently documented knowledge on the arctic fox (Vulpes lagopus) and the greater snow goose (Chen caerulescens atlantica), two important tundra species. Using participatory approaches in Mittimatalik (also known as Pond Inlet), Nunavut, Canada, we documented traditional ecological knowledge about these species and found that, in fact, it did expand the spatial and temporal scales of current scientific knowledge for local arctic fox ecology. However, the benefits were not as apparent for snow goose ecology, probably because of the similar spatial and temporal observational scales of the two types of knowledge for this species. Comparing sources of knowledge at similar scales allowed us to gain confidence in our conclusions and to identify areas of disagreement that should be studied further. Emphasizing complementarities across scales was more powerful for generating new insights and hypotheses. We conclude that determining the scales of the observations that form the basis for traditional ecological knowledge and scientific knowledge represents a critical step when evaluating the benefits of integrating these two types of knowledge. This is also critical when examining the congruence or contrast between the two types of knowledge for a given subject.